1998
DOI: 10.1161/01.res.82.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown and Release of Myofilament Proteins During Ischemia and Ischemia/Reperfusion in Rat Hearts

Abstract: Abstract-Our objective in experiments reported here was to identify myofilament proteins of rat hearts either lost or degraded by cardiac ischemia (15-or 60-minute duration) with and without 45 minutes of reperfusion. We correlated these changes with alterations in myofilament sensitivity to Ca 2ϩ and maximum force generation. Protein degradation and loss were assessed by high-performance liquid chromatography, SDS-PAGE, Western blotting analysis, and amino acid sequencing. Compared with nonischemic control he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
156
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(171 citation statements)
references
References 60 publications
12
156
0
2
Order By: Relevance
“…Furthermore, Hoffman et al suggested that the mobile domain undergoes a disordered-ordered structural transition when it interacts with actin in the absence of Ca 2+ [32], indicative of an association of this region with actin-Tm (termed "fly-casting mechanism"). It has been shown, at least in rodents, that moderate ischemia/reperfusion induces proteolytic cleavage of 17 residues from the C-terminal of TnI that includes the second actin-interacting sites [80]. Human myofibrils containing truncated cTnI display impaired force relaxation kinetics upon rapid solution switching Ca 2+ deactivation [51].…”
Section: Troponin Imentioning
confidence: 99%
“…Furthermore, Hoffman et al suggested that the mobile domain undergoes a disordered-ordered structural transition when it interacts with actin in the absence of Ca 2+ [32], indicative of an association of this region with actin-Tm (termed "fly-casting mechanism"). It has been shown, at least in rodents, that moderate ischemia/reperfusion induces proteolytic cleavage of 17 residues from the C-terminal of TnI that includes the second actin-interacting sites [80]. Human myofibrils containing truncated cTnI display impaired force relaxation kinetics upon rapid solution switching Ca 2+ deactivation [51].…”
Section: Troponin Imentioning
confidence: 99%
“…The most studied one is the degradation of TnI, the inhibitory subunit of Tn complex. Selective TnI proteolysis at the C terminus has been reported after ischemia/reperfusion injury, also known as myocardial stunning, in rodent hearts [31][32][33]. The N-terminal degradation of cardiac TnI was reported in a tail suspension rat model that simulated microgravity [34].…”
Section: Degradationmentioning
confidence: 99%
“…In 2000, TnI and TnT have been approved as the biomarkers for AMI diagnosis [42], and several kits have been commercially developed and used in clinical studies [43][44][45]. In addition to TnI and TnT, other myofilament proteins, including TnC [46], LC2 [46], aactinin [32] and MyBP-C [47], were also reported as useful markers in animal models of ischemia/reperfusion injury. Two mechanisms are believed to be responsible for most myofilament protein degradation.…”
Section: Degradationmentioning
confidence: 99%
See 2 more Smart Citations